Examining the State of Risk Management Research in New Product Development Process. Issue 2 (3rd April 2018) - Chauhan, Avanish Singh; Nepal, Bimal; Soni, Gunjan; Rathore, Ajay Pal Singh
Abstract: New products are major sources of competitive advantage and success for a manufacturing enterprise. However, not all new product development (NPD) initiatives result in a successful product and are therefore a major cause of wasted resources. Furthermore, NPD processes are becoming increasingly complex and risky due to today's globalized market and customers' desire for technologically advanced products. While there has been a significant interest in academia about NPD risks, the existing literature is spread across multiple outlets, making it difficult for any practitioner or researcher to synthesize the current work. This article aims to minimize that gap by providing a comprehensive overview of current research activities in the field of risk management in NPD process in one place. The research design is based on mapping and classification of the existing body of knowledge into the domains of NPD risk analysis and management. The article analyzes the contemporary NPD risk analysis methods on three fronts: risk identification, risk assessment, and risk mitigation. Based on the review, the article then identifies and discusses several key areas for future research significant to engineering management practices. Finally, an integrated framework is presented to provide a holistic approach toward risk management in the NPD process, followed by the practical implications for engineering managers and practitioners.